Continuous ambulatory hand force monitoring during manual materials handling using instrumented force shoes and an inertial motion capture suit - Faber, G. S.; Koopman, A. S.; Kingma, I.; Chang, C. C.; Dennerlein, J. T.; van Dieën, J. H. (Journal of Biomechanics, 2018)
Hand forces (HFs) are commonly measured during biomechanical assessment of manual materials handling; however, it is often a challenge to directly measure HFs in field studies. Therefore, in a previous study we proposed a HF estimation method based on ground reaction forces (GRFs) and body segment accelerations and tested it with laboratory equipment: GFRs were measured with force plates (FPs) and segment accelerations were measured using optical motion capture (OMC). In the current study, we evaluated the HF estimation method based on an ambulatory measurement system, consisting of inertial motion capture (IMC) and instrumented force shoes (FSs).